12,13-diHOME Promotes Inflammatory Macrophages and Epigenetically Modifies Their Capacity to Respond to Microbes and Allergens - Din L. Lin; Kevin M. Magnaye; Cara E. Porsche; Sophia R. Levan; Elze Rackaityte; Mustafa Özçam; Susan V. Lynch (Journal of Immunology Research, 2024)
Elevated infant fecal concentrations of the bacterial-derived lipid 12,13-dihydroxy-9Z-octadecenoic acid (12,13-diHOME) increase the risk for childhood atopy and asthma. However, the mechanisms by which this lipid contributes to disease development are largely unknown. We hypothesized that macrophages, which are key to both antimicrobial and antigen responses, are functionally and epigenetically modified by 12,13-diHOME leading to short- and long-term dysfunction with consequences for both antimicrobial and antigenic responses. Macrophages exposed to 12,13-diHOME are skewed toward inflammatory IL-1βhighCD206low cells, a phenomenon that is further amplified in the presence of common microbial-, aero-, and food-allergens. These IL-1βhighCD206low macrophages also exhibit reduced bacterial phagocytic capacity. In primary immune cell coculture assays involving peanut allergen stimulation, 12,13-diHOME promotes both IL-1β and IL-6 production, memory B cell expansion, and increased IgE production. Exposure to 12,13-diHOME also induces macrophage chromatin remodeling, specifically diminishing access to interferon-stimulated response elements resulting in reduced interferon-regulated gene expression upon bacterial lipopolysaccharide stimulation. Thus 12,13-diHOME reprograms macrophage effector function, B-cell interactions and promotes epigenetic modifications that exacerbate inflammatory response to allergens and mutes antimicrobial response along the interferon axis. These observations offer plausible mechanisms by which this lipid promotes early-life pathogenic microbiome development and innate immune dysfunction associated with childhood allergic sensitization.